2016
DOI: 10.1515/pjvs-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of temperature on survival rate of Listeria monocytogenes in yogurt

Abstract: The aim of the study was to (i) evaluate the behavior of Listeria monocytogenes in a commercially produced yogurt, (ii) determine the survival/inactivation rates of L. monocytogenes during cold storage of yogurt and (iii) to generate primary and secondary mathematical models to predict the behavior of these bacteria during storage at different temperatures.The samples of yogurt were inoculated with the mixture of three L. monocytogenes strains and stored at 3, 6, 9, 12 and 15 o C for 16 days. The number of lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…bulgaricus and Streptococcus salivarius ssp. thermophilus added to milk as a starter culture, as well as the production of organic acids, mainly lactic acid [4] [48] [49]. The researchers found that lag phase and growth rate of Listeria were affected not only by storage temperature but also by lactic acid concentration and pH of product ranged from 5.2 do 5.8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…bulgaricus and Streptococcus salivarius ssp. thermophilus added to milk as a starter culture, as well as the production of organic acids, mainly lactic acid [4] [48] [49]. The researchers found that lag phase and growth rate of Listeria were affected not only by storage temperature but also by lactic acid concentration and pH of product ranged from 5.2 do 5.8.…”
Section: Resultsmentioning
confidence: 99%
“…In the European Union (EU), 1763 confirmed human cases of listeriosis were reported in 2013 by 27 member states. The EU notification rate was 0.44 cases per 100,000 population which represented an 8.6% increase compared to 2012 [4]. In 2013, there were 191 deaths caused by listeriosis in the EU.…”
Section: Introductionmentioning
confidence: 95%
“…Choi et al (1988) found that L. monocytogenes will survive 13 to 27 d in vanilla-flavored yogurt after inoculation of 10 4 to 10 5 cells, whereas Tirloni et al (2015) reported that L. monocytogenes with a starting concentration of either 2 or 5 log cfu/g was still detected in 25-g samples of unflavored and strawberry yogurt at 68 d of storage. Szczawiński et al (2016) developed linear and polynomial models to describe the inactivation rate of L. monocytogenes in yogurt as a function of temperature and found D-values (decimal reduction time) ranging from 87.0 h at a storage temperature of 15°C to 243.9 h at a storage temperature of 6°C when calculated from linear models.…”
Section: Keeping Quality and Safety Of Yogurtmentioning
confidence: 99%
“…A linear decrease in the number of these bacteria was observed during storage (34,35). This phenomenon was mainly explained by the low pH of the samples (range 4.1-4.4), because the pH value of about 4.6 is generally considered as the minimum enabling the growth of L. monocytogenes (7,28).…”
Section: Discussionmentioning
confidence: 99%
“…Certain food categories are no longer under a zero tolerance regime but have a specified maximum allowed concentration of 100 CFU/g or ml for products placed on the market during their shelf-life. Therefore, many studies on modelling the effects of various factors on the growth of L. monocytogenes have been published in recent years (5,18,22,23,35). This research allows the behaviour of L. monocytogenes in RTE meat products to be predicted.…”
Section: Discussionmentioning
confidence: 99%